Compulsive Drives Of Uncle Vanya On Keeping The Trust In Chekhov‟S Uncle Vanya Drama (1896): A Social Psychological Approach - Alavi, Nefiar Reza (2012)
The object of the research is a drama entitled Uncle Vanya. The major problem of her study is how the compulsive drives of Uncle Vanya are reflected in Chekhov's Uncle Vanya drama based on Social Psychological approach. Therefore, the study analyzes the play in term of its structural elements of the play and based on the social psychological approach. These studies belong to qualitative study. The writer uses two data sources: they are primary data sources and secondary data sources. The primary data sources and the object of the study is the text play itself, meanwhile the secondary data sources are the other sources which relate to the primary data sources such as website about the play. The method of the data collection is library research by collecting both primary and secondary data. The technique of data analysis is descriptive analysis based on Social Psychological approach. Based on the analysis, the outcome of this study shows that the problem of major character encounters causes the conflict of his mental condition. Then, it develops to become basic anxiety and hostility, it influences and drives him to do some ways to always keep her sister's estate.